Economic Integration: Advantages and Risks for the Kazakhstan Economy - AKHMETOVA, Kulyanda A.; TERZHANOVA, Aigul Zh.; AKHMETOVA, Asel A.; SADUAKASSOVA, Aigerim B.; SMAILOVA, Gulzhihan K. (Journal of Advanced Research in Law and Economics, 2017)
The paper addresses goals, tasks of the Customs Union that has currently overgrown into the Eurasian Customs Union (EACU) of Kazakhstan, Russia, Belarus, Armenia, and Kyrgyzstan, as well as economic, political, and social consequences of the Kazakhstan membership in the union. It makes the careful analysis of activities under the conditions of membership in the economic association relevant. As a result of globalization of the world economy the interdependence and interrelation of national economies increase that leads to expansion of international and economic relations, competition of both goods and nations. Under these conditions nations, which look toward not only survival but domination on the market, join integration unions to expand end markets for domestics products, attracting investments, new technologies and labour force to their state. Based on the carried out analysis of the trading relations dynamics of Kazakhstan with EACU nations and third countries, the authors identify factors and causes under the impact of which a particular nation or an economic entity experienced success or failure; express their point of view regarding what nations enjoyed advantages of being a member of CU and EACU; what should be done to improve the efficiency of the integration union. Under conditions of expanding globalization processes Kazakhstan needs to make every effort to derive maximum benefits from participation in the world integration. We need a scientifically grounded system approach to the studies of nation’s economic interests, since the analysis of Kazakhstan economic performance within EACU indicates that the national economy didn’t reap much benefits from integration, national economists aren’t eager to advocate the nation’s interests.